Микстура от косоглазия: роман / Дарья Донцова - Донцова Дарья Аркадьевна (Иронический детектив, 2003)
Экземпляры: ф.11 (20190426) / Инвентарный номер: 59597 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Д 67 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44